1998
DOI: 10.1074/jbc.273.41.26516
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Hic-5, A Senescence-related Protein, with Focal Adhesion Kinase

Abstract: Integrin-mediated cell adhesion induces various biological events such as cell proliferation, survival, migration, cytokine production, and cytoskeleton reorganization (1-7). Despite the significance of these events, signal transduction pathways of integrins have not been fully understood. One of the approaches for integrin-mediated signal transduction is to study the proteins that are localized to focal adhesions.Focal adhesions are the sites where cells attach to substrata via integrin-extracellular matrix b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
96
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 41 publications
10
96
0
1
Order By: Relevance
“…We found that loss of Hic-5 decreased the formation of the complex between MT1-MMP and FAK, supporting that Hic-5 bridges MT1-MMP and FAK. Hic-5 is well-suited for this role as an adaptor protein given that the N-terminal LD domain of Hic-5 binds FAK (Fujita et al, 1998), and the C-terminal LIM2 and LIM3 domains are required for interaction with MT1-MMP (shown here). Hic-5 is known to localize to integrin-mediated sites of adhesion, where it coordinates cell migration in 2D (Brown and Turner, 2004;Tumbarello and Turner, 2007;Deakin and Turner, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that loss of Hic-5 decreased the formation of the complex between MT1-MMP and FAK, supporting that Hic-5 bridges MT1-MMP and FAK. Hic-5 is well-suited for this role as an adaptor protein given that the N-terminal LD domain of Hic-5 binds FAK (Fujita et al, 1998), and the C-terminal LIM2 and LIM3 domains are required for interaction with MT1-MMP (shown here). Hic-5 is known to localize to integrin-mediated sites of adhesion, where it coordinates cell migration in 2D (Brown and Turner, 2004;Tumbarello and Turner, 2007;Deakin and Turner, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Because Hic-5 is a known focal adhesion scaffold protein that forms a complex with FAK (Fujita et al, 1998), and the fine punctate staining pattern within 3D sections (Fig. 4A) appears to be similar to those reported for other focal adhesion proteins in 3D (Cukierman et al, 2001;Petroll and Ma, 2003), we further investigated whether Hic-5 colocalized with activated FAK.…”
Section: S1p Mediated Rapid Translocation Of Hic-5 To Focal Adhesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the current study, we identified in small arteries a high expression of Hic-5, a homologue of paxillin (51). Hic-5, in addition to having a similar domain structure as paxillin, also localizes to the same sites and shares binding partners with paxillin (16,51). However, they must not entirely duplicate each others functions since paxillin knockout is embryonic lethal (18), and unlike paxillin, Hic-5 is not activated by integrin engagement or phosphorylation by p125FAK (16,51).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is phosphorylated by PYK2, a calcium-dependent homologue of p125FAK (16,51), suggesting different cellular functions for the two proteins. Hic-5 was shown to be a substrate for PYK2 (23), and in COS cells and rat fibroblasts, it was shown to interact with PYK2 (31), whereas in rat kidney epithelial cells (24), Hic-5 was shown to associate with Hsp27.…”
mentioning
confidence: 99%